Entrepreneurship among the Displaced and Dispossessed: Exploring the Limits of Emancipatory Entrepreneuring. (31st May 2015) - Al‐Dajani, Haya; Carter, Sara; Shaw, Eleanor; Marlow, Susan
<x xml:space="preserve">Abstract</x> This paper explores the links between entrepreneurship, emancipation and gender within the international development arena. Through a longitudinal analysis of a micro‐enterprise development project in which intermediary organizations contract traditional handicrafts from female home‐based producers, we focus on the impact of contracting policies on the ability of the desperately poor to improve their disadvantaged position. Our critical analysis reveals how intermediaries who impose exclusive contracting conditions, supposedly to protect the women's interests, actually constrain the emancipatory potential of the women's entrepreneurial activities. However, such contractual limitations generate collaborative networks enabling the women to challenge these constraints in an effort to assert control over their activities. Accordingly, this paper contributes to contemporary debates concerning the emancipatory potential of entrepreneurship within the context of development. We advance this analysis through a gendered evaluation of the role of intermediary organizations on entrepreneurial emancipation and related empowerment.